2017
DOI: 10.1016/j.jpeds.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Low and High Birth Weights Are Risk Factors for Nonalcoholic Fatty Liver Disease in Children

Abstract: Objective To examine the distribution of birth weight in children with NAFLD compared with the general U.S. population and the relationship between birth weight and severity of NAFLD. Study design A multi-center, cross-sectional study of children with biopsy-proven NAFLD enrolled in the Nonalcoholic Steatohepatitis Clinical Research Network Database. Birth weights were categorized as low birth weight (LBW), normal birth weight (NBW), or high birth weight (HBW) and compared with distribution of birth weights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 33 publications
1
61
0
1
Order By: Relevance
“…Children with low and high birth weights are more likely to progress to more severe stages of fibrosis and steatosis later in adolescence, suggesting a very early influence of nutritional status on future disease progression. 16 In one study, breastfeeding exclusively for at least 6 months decreased the odds of developing NAFLD during adolescence. 11 In addition, animal studies have shown that early postnatal exposure to a high-fat diet increased the susceptibility to NAFLD through the upregulation of hepatic lipogenesis.…”
Section: Natur Al His Torymentioning
confidence: 98%
“…Children with low and high birth weights are more likely to progress to more severe stages of fibrosis and steatosis later in adolescence, suggesting a very early influence of nutritional status on future disease progression. 16 In one study, breastfeeding exclusively for at least 6 months decreased the odds of developing NAFLD during adolescence. 11 In addition, animal studies have shown that early postnatal exposure to a high-fat diet increased the susceptibility to NAFLD through the upregulation of hepatic lipogenesis.…”
Section: Natur Al His Torymentioning
confidence: 98%
“…Because altered birth weights are risk factors for the development of NAFLD in children (16), we began by analyzing the body weight trajectories of the offspring. Consistent with our previous observation (10), offspring from insulin-resistant parents at postnatal day 5 presented transient increased body weights compared with controls ( Figure 1A).…”
Section: Parental Genetic Insulin Resistance Impacts Body Weight Trajmentioning
confidence: 99%
“…NAFLD affects ∼34% of obese children in North America, up to half of whom have progressed to nonalcoholic steatohepatitis (NASH; characterized by inflammation and cellular damage in addition to steatosis) at the time of diagnosis . Children with NASH are more likely to have advanced fibrosis, even after adjusting for obesity . Both NAFLD and NASH may progress to hepatocellular carcinoma, and fatty liver disease is rapidly becoming a leading cause for liver transplant in the United States .…”
Section: Introductionmentioning
confidence: 99%